Note on Arens regularity of symmetric tensor products - Taras, O.G.; Zagorodnyuk, A.V. (Carpathian Mathematical Publications, 2014)
We investigate symmetric regularity of sums of symmetric tensor products of Banach spaces and Arens regularity of symmetric tensor products of Banach algebras. An example for the Hilbert space is obtained.